2006
DOI: 10.1099/jmm.0.46262-0
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Chlamydia trachomatis from clinical specimens in Taiwan

Abstract: This study was conducted to determine the prevalence and distribution of Chlamydia trachomatis genotypes in Taiwan. Urine and endocervical-swab samples were collected from two hospitals located in northern and southern Taiwan. The genotypes of a total of 145 samples positive for C. trachomatis were analysed by sequencing the omp1 gene and this was successful in 102 samples. Nine different C. trachomatis genotypes were identified. Genotype E was the most prevalent (22 %), followed by D and Da (19 %), F (16 %), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 44 publications
(40 reference statements)
7
35
4
Order By: Relevance
“…In both studies, genotypes E, D and F were identified most frequently in samples from subjects with urogenital infections of C. trachomatis, respectively comprising 83.3% and 71.8%, of the genotypes found. These results accord with the findings of studies in other countries (such as Argentina, Costa Rica, Taiwan, Iran and Hungary), in which the same three genotypes were found to appear most frequently in urogenital cases of C. trachomatis [6,7,23]. In the present study, genotype F was the most frequent, followed by genotypes D and J.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In both studies, genotypes E, D and F were identified most frequently in samples from subjects with urogenital infections of C. trachomatis, respectively comprising 83.3% and 71.8%, of the genotypes found. These results accord with the findings of studies in other countries (such as Argentina, Costa Rica, Taiwan, Iran and Hungary), in which the same three genotypes were found to appear most frequently in urogenital cases of C. trachomatis [6,7,23]. In the present study, genotype F was the most frequent, followed by genotypes D and J.…”
Section: Discussionsupporting
confidence: 82%
“…Currently, 19 serovars and related variants (A, B/Ba, C, D/Da, E, F, G/Ga, H, I/Ia, J, K, L1, L2, L2a and L3) of C. trachomatis have been identified by using polyclonal and monoclonal antibodies against the major outer membrane protein (MOMP) [5,6]. Serovars A, B and C have usually been associated with trachoma, whereas D through K have tended to correlate with urogenital infections.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is one of the first studies on genotype distribution of C. trachomatis in mainland China (10) and a study with a relative large sample size compared with previous studies ( Table 2). The failure rate (5.6%) of nested omp1 PCR in our study was comparable to those reported in many previous studies (5, 11) but much lower than in other studies (10).…”
Section: Discussionsupporting
confidence: 80%
“…Many studies have shown the feasibility of deducing the serotypes of C. trachomatis clinical isolates using PCR-based RFLP or sequencing of the amplified omp1 gene, which encodes the MOMP (8,10,15). This technology has provided a valuable and sensitive means for molecular epidemiological analysis to identify high-risk groups and track sexual networks (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…The most common serovar detected worldwide is E (up to 22 to 49% of cases) followed by serovars F and D (17 to 22% and 9 to 19%, respectively), while other serovars are less frequently identified (1,10,12,15,16,17).…”
mentioning
confidence: 99%